An Installation of A Solar Power Plant in Selayang Baru Village, Langkat District - Imnadir; Yuvina; Akhiruddin (CERED Indonesia Institute, 2023)
The Langkat Regency Government has collaborated with PLN to meet electricity needs in remote villages, but there are several obstacles, so these efforts cannot be achieved evenly. Therefore, in efforts to improve the quality of life and economic growth of rural communities, energy has a big role. Where this research discusses the availability of electricity in rural areas, it is hoped that it can encourage increased productivity, improve educational facilities, worship, health, as well as foster new economic activities. In order to meet the energy needs of rural communities, local governments are trying to implement various energy infrastructure development activities by utilizing the potential of local energy sources. One potential energy that can be developed is solar power plants (PLTS) for electricity in rural areas. This service activity can essentially facilitate the procurement of PLTS equipment which will be placed in a Grand Mosque in Desan Selayang as a pilot.